Measuring radon-222 in soil gas with high spatial and temporal resolution - Huxtable, Darren; Read, David; Shaw, George (Elsevier, 2017)
In order to exploit 222Rn as a naturally-occurring tracer in soils we need to sample and measure radon isotopes in soil gas with high spatial and temporal resolution, without disturbing in situ activity concentrations and fluxes. Minimization of sample volume is key to improving the resolution with which soil gas can be sampled; an analytical method is then needed which can measure radon with appropriate detection limits and precision for soil gas tracer studies. We have designed a soil gas probe with minimal internal dead volume to allow us to sample soil gas volumes of 45 cm3. Radon-222 is extracted from these samples into a mineral oil-based scintillation cocktail before counting on a conventional liquid scintillation counter. A detection limit of 320 Bq m-3 (in soil gas) is achievable with a one hour count. This could be further reduced but, in practice, is sufficient for our purpose since 222Rn in soil gas typically ranges from 2,000 - 50,000 Bq m-3. The method is simple and provides several advantages over commonly used field-portable instruments, including smaller sample volumes, speed of deployment and reliability under field conditions. The major limitation is the need to count samples in a liquid scintillation counter within 2 – 3 days of collection, due to the short (3.824 day) radioactive half-life of 222Rn. The method is not applicable to the very short-lived (55 second half-life) 220Rn.